Xenotransplantation New Insights - Miyagawa, Shuji (IntechOpen, 2017)
It has been nearly 5 years since I edited the last version. In this version, the focus is on islet transplantation. In addition, interesting topics dealing with corneal and peripheral nerve transplantation and decellularization are covered. Unfortunately, clinical trials have not started in Japan, the USA, or Europe in the past 5 years. On the other hand, clinical trials were completed in many countries and so on (inventory of human xenotransplantation practices: IXA and HUG in collaboration with the WHO). In addition, in Japan, clinical trials related to cell transplantation have been initiated, and guidelines for xenotransplantation have been revised. In the near future, some clinical trials on xenotransplantation using genetically modified pigs or the microencapsulation of pancreatic islets will start.